Urgent laparoscopic mesh splenopexy for torsion of wandering spleen and distal pancreas: A case report. Issue 3 (25th August 2015) - Torri, Fabio; Parolini, Filippo; Vanzetti, Enrico; Milianti, Susanna; Cheli, Maurizio; Alberti, Daniele
Abstract Wandering spleen is a condition in which an incomplete fusion of the splenic ligaments allows the spleen to move within the abdomen, predisposing it to splenic torsion along its vascular pedicle. Torsion of a wandering spleen is an uncommon occurrence, especially in children, and associated torsion of the distal pancreas is even more unusual, with only four cases having been reported in adults. Non‐specific clinical presentation makes radiologic evaluation essential in order to obtain a diagnosis and to send the patient for early surgery before life‐threatening complications arise. Here we present a rare case of torsion of wandering spleen together with volvulus of the distal pancreas in a 13‐year‐old girl. In this case, prompt radiological assessment allowed for an early diagnosis, and the patient was successfully treated with urgent laparoscopic derotation of both the spleen and the distal pancreas as well as mesh splenopexy. To the best of our knowledge, this procedure has never been described in a pediatric setting.